Employment trajectories in Germany: do firm characteristics and regional disparities matter? - Matthias Dütsch; Olaf Struck (Journal for Labour Market Research, 2014)
Life course research accentuates that employment trajectories are governed by individual determinants and endogenous causalities; thus, the start to the employment career enduringly affects workers' future mobility patterns. However, their actions are always embedded within a particular framework: Their employment trajectories are influenced by firm-specific opportunity structures, regional heterogeneities, and the business cycle. This article focuses on the structural factors framing worker's mobility processes. Structural and cyclical determinants were assessed by combining a German linked employer-employee dataset with data on regional economic characteristics from the statistical 'spatial planning regions'. The hierarchically clustered data were explored with multilevel analysis models. These identified the key factors influencing employment stability; the determinants of upward, lateral, and downward interfirm mobility; and transitions leading to unemployment. Our results show that employees can minimize the endogenous causality by taking advantage of particular framework conditions: A firm's investments in further training and internal infrastructure impact positively on employment trajectories, and work councils increase employment stability, especially during periods of economic growth. In contrast, employment trajectories are destabilized by disadvantageous firm demographics and intensive use of fixed-term employment. During an economic downswing, employment opportunities are better in densely populated areas, whereas unemployment risks dominate in rural areas. In the period of economic growth, all employees within a region benefit from a higher local level of human capital regardless of qualification level, whereas during an economic downturn, skill segregation prevails and only the highly qualified benefit.
Keywords: J62; J64; M51; O15; 330; Berufsverlauf - Determinanten; Beschäftigungsdauer; regionale Faktoren; regionale Disparität; Konjunkturabhängigkeit; Weiterbildungsangebot; Betriebsrat; Bevölkerungsdichte; Qualifikationsstruktur; Erwerbstätigenstruktur; IAB-Linked-Employer-Employee-Datensatz; Arbeitsplatzwechsel; zwischenbetriebliche Mobilität; berufliche Mobilität; Rezession; Konjunkturaufschwung